In‐Situ Architectures Designed in 3D Cell‐Laden Hydrogels Using Microscopic Laser Photolithography. (5th February 2015) - Mironi‐Harpaz, Iris; Hazanov, Lena; Engel, Guy; Yelin, Dvir; Seliktar, Dror
Abstract : Thermoresponsive bioactive hydrogels made from fibrinogen and Pluronic F127 are physically crosslinked at 37 °C to facilitate local chemical crosslinking using microscopic photolithography. The reaction conditions are mild enough to pattern in the presence of living cells. The interfaces between the chemically crosslinked "stiffer" and physically crosslinked "softer" regions capture the unique displays of morphogenesis in response to changing stiffness at the cellular scale.